THE EFFECTIVENESS OF â€œGHOST DEFINITIONâ€ IN TEACHING VOCABULARY - Imran, Fathurrahman (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
This research aimed to find out whether ghost definition is effective or not in teaching vocabulary at the first semester of FPBS IKIP Mataram in academic year 2013/2014â€. The research design used was experimental research by using post-test design only. The population of this research was 80 students, which consist of 3 classes. Then, the researcher took only 2 classes or 52 students as the sample. In collecting the data, the researcher used the data obtained from the posttest given after treatment. By analyzing the data, researcher can find out the differences between the result of post-test of the control group and the experimental group before and after the treatment. The analysis of results may be subdivided into descriptive statistics and inferential statistics. The finding show that the mean score of experimental group was higher than control group (X1 73.28 > X2 62.66) while, the score of t-test was 2.16 and t-table was 2.00856 (t-test 2.16 > t-table 2.00856) with 50 degree of freedom and the confidence level of 0.05%. Thus, conclusion of this research showed that ghost definition was effective in teaching English vocabulary. It can be concluded that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Based on the findings, it is suggested that the lecturer expected to apply ghost definition in teaching English vocabulary at any time and then the students always practice to be more active in memorizing new words.